PENGARUH PENGGUNAAN MODUL PEMBELAJARAN MATEMATIKA BERBASIS INKUIRI TERBIMBING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMAN 1 PAINAN - Yanti Nazmai Ekaputri; Sefrinal Sefrinal; Muhammad Arif (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
The observation results show that there is no teaching material in the form of modules used bymathematics teachers at SMAN 1 Painan. Based on the problems and research objectives, this type ofresearch is a quasi experiment. This research was conducted on two groups, namely the experimentalclass using guided inquiry-based modules and the control class using conventional learning. Thepopulation in this study were all students of class X MIA SMAN 1 Painan for the academic year2020/2021 which consisted of 5 classes. To get the sample class, namely the experimental and controlclasses, the random sampling technique was used. Class X.MIA 4 was chosen as the experimentalclass and class X.MIA 3 was chosen as the control class. The instrument used was a test consisting of5 questions on concept understanding tests. The data analysis used the t test because the data werenormally distributed and homogeneous. Based on the results of the hypothesis test, a significance levelof 0.0035 was obtained. It means that Ho is rejected, this means that the understanding of students'mathematical concepts taught by using guided inquiry-based modules is better than conventionallearning.